(untitled) (Nepal Medical College Journal, 2025)
Road traffic accidents (RTAs) pose a major public health issue worldwide, resulting in over 3,000 fatalities each day across the globe. Low- and middle-income nations account for roughly 85% of these deaths and 90% of the annual disability-adjusted life years lost. Nepal is ranked 79th in the world for RTA-related fatalities, making it the 11th leading cause of death in the nation. Factors such as difficult terrain, adverse weather, insufficient infrastructure, and poor traffic management significantly contribute to the elevated accident rates. The purpose of this study was to examine the epidemiological features of road traffic accidents in Kathmandu, with an emphasis on demographic trends, temporal distribution, types of vehicles involved, and patterns of injury. A retrospective hospital-based study was carried out at Nepal Medical College Teaching Hospital from January 1, 2021, to December 31, 2021. All cases of RTA in Kathmandu who presented to our hospital were included in this study. All complete RTA cases within the city of Kathmandu were included in the analysis. Data were gathered concerning age, sex, injury locations, time of occurrence, and day of the week. Statistical analysis was conducted using SPSS version 21. During the study period, a total of 296 RTA cases were documented. Males accounted for 219 cases (73.99%) compared to 77 females (26.01%), resulting in a male-to-female ratio of 2.84:1. The age group most affected was 20-29 years (217 cases, 73.31%). Friday had the highest number of accidents (113 cases, 38.18%), with peak occurrences during daytime hours (143 cases, 48.31%). Two-wheelers were involved in 244 cases (82.43%), making them the most prevalent type of vehicle. Extremity injuries were the most common (290 cases, 97.97%), followed by head injuries (113 cases, 38.18%). Young males aged 20-29 years using two-wheelers are at highest risk for RTAs. The predominance of extremity and head injuries emphasizes the critical need for helmet use and improved road safety measures. Targeted interventions including strict traffic law enforcement, infrastructure improvements, and public awareness campaigns are essential to reduce RTA incidence and severity.